Influence of caffeine on biathlon performance during a simulated competition - Engel, H.; Yilmaz, C.; Appelhans, D.; Mathieu, J.; Kock, H.; Staunton, C.; Koehler, K. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Caffeine has demonstrated consistent benefits in enhancing endurance performance in general and specific improvements in cross-country skiing. However, recent data suggest a negative impact on standing shooting performance at rest. Therefore, the primary aim of the present study was to assess the impact of caffeine on biathlon performance during a simulated competition. METHODS: Using a randomized, double-blind, cross-over design, national and international level biathletes (n=9, 24 ± 4 yrs, body mass 77.5 ± 4.7 kg, fat % 11 ± 3 %, VO2max 65 ± 3 ml/kg/min) with a habitual caffeine intake of 65 ± 30 mg/day received either caffeine (3mg/kg, CAF) or a placebo (PLC). Biathletes underwent a simulated competition in a laboratory setting, which included 5 laps of 6-min self-paced roller skiing on a motor-driven treadmill, interspersed by 4 shooting bouts (prone, standing, prone, standing) with five shots each. Shots were fired on a 50m indoor shooting range using an electronic target. Breath-by-breath gas exchange and heart rate (HR) were recorded continuously during roller skiing. Blood lactate (bLa) and rating of perceived exertion (RPE) were assessed following each shooting bout. Biathletes also performed precision shooting (20 prone, 20 standing) at rest and following the simulated competition. RESULTS: Caffeine reduced the average number of hits during standing shooting (7.3 ± 1.6 vs. 8.3 ± 0.8; p = 0.06) but did not affect prone shooting (p = 1.00). Biathletes completed the first two laps significantly faster with CAF (+0.14 ± 0.13 m/s, p = 0.03 and +0.07 ± 0.06 m/s, p = 0.02, respectively), but improvements in overall skiing performance (+0.05 ± 0.7 m/s) did not reach statistical significance (p = 0.12). Exercise intensity was higher in CAF when compared to PLC (85.6 ± 4.4 vs. 84.3 ± 5.7 %VO2max; p = 0.06) during lap 2. No significant differences in HR and RPE were detected, but bLa was significantly higher from lap 2 to lap 5 in CAF (p < 0.001, respectively). During precision shooting, the number of hits did not differ between CAF and PLC in prone (p = 0.40) or standing (p = 1.00) at rest. In the post-exercise state, CAF tended to improve prone shooting performance (18.7 ± 1.5 vs. 17.8 ± 1.2 hits; p = 0.09). On average athletes reported more severe adverse effects, notably symptoms of nausea and vomiting (p = 0.03), in CAF when compared to PLC. Further, two athletes in CAF had to discontinue the condition due to gastrointestinal issues. CONCLUSION: Despite a highly individual response, caffeine negatively affected standing shooting performance but tended to improve skiing performance during a simulated biathlon competition. Aside from individual tolerance levels, biathletes should weigh potential costs (impaired shooting performance) and benefits (improved skiing performance) of caffeine on overall biathlon performance, with particular attention to the importance of shooting across various biathlon events.